Prevalência e fatores de risco para morbidade materna grave e near miss materno no Estado de Sergipe - Galvão, Larissa Paes Leme (2013)
Background: The interest in obstetrical complications that culminate with maternal death and the urgent need for improvement in these indexes led to the development of the concept of maternal near miss. From a normal situation, the patients are in a continuum that can evolve with the development of moderate and severe situations of health. Severe acute maternal morbidity (SAMM) (situation less severe) and near miss (NM) (situation more severe) are two degrees of situation immediately before maternal death. The main advantage of studying these cases is higher frequency when comparing with maternal deaths cases and that the determining factors are the same. This study aims to determine the ocurrence of SAMM and NM situations in two maternities of reference of the state of Sergipe, determine the prevalence of the event and describe the risk factors associated. Casuistic and methods: A cross sectional study with double controls was conducted in patients who were pregnant sometime and were hospitalized in two reference maternities of Sergipe state. The patients answered a survey about issues relevant to the subject. For categorical variables was used Fisher s exact test. For normal continuous variables was applied the Student t test and for the not normal, the U-Mann-Whitey test. Odds ratio and confidence interval were used whenever possible. Multivariate analysis was performed and p <0,05. Results: There were 16,243 live birth deliveries, and occurred 1102 SAMM, 77 NM and 17 maternal deaths cases. The prevalence of SAMM + NM founded were, respectively, 7.6 cases/1000 LB, the mortality index was 18% (4.5 cases for each death) The main causes of SAMM and NM were respectively: 67.5% by hypertensive causes and 87.1% by necessity of invasive procedures. High age, low income, absence of prenatal, high rates of cesarean section, previous abortion and low weight of the baby at birth with unfavorable perinatal prognosis were statistically significant for the study group. Multivariate analysis showed that the number of eligibility criteria for NM was related with the severity of the situation. Conclusions: The situations of SAMM and NM in the two maternities studied reached significant values. Study NM can be the most efficiently way of conducting internal audits for the improving of the quality of services. Protocols based on adverse situations like these, where the detection can be made on the exact point of failure, can recommend conducts and interventions able to save lives.